Proximate, Antinutrients and Mineral Composition of Raw and Processed (Boiled and Roasted) Sphenostylis stenocarpa Seeds from Southern Kaduna, Northwest Nigeria. (16th March 2014) - Ndidi, Uche Samuel; Ndidi, Charity Unekwuojo; Olagunju, Abbas; Muhammad, Aliyu; Billy, Francis Graham; Okpe, Oche
Abstract : This research was aimed at evaluating the proximate composition, level of anti-nutrients, and the mineral composition of raw and processed Sphenostylis stenocarpa seeds and at examining the effect of processing on the parameters. From the proximate composition analysis, the ash content showed no significant difference (P > 0.05 ) between the processed and unprocessed (raw) samples. However, there was significant difference (P < 0.05 ) in the levels of moisture, crude lipid, nitrogen-free extract, gross energy, true protein, and crude fiber between the processed and unprocessed S. stenocarpa . Analyses of the antinutrient composition show that the processed S. stenocarpa registered significant reduction in levels of hydrogen cyanide, trypsin inhibitor, phytate, oxalate, and tannins compared to the unprocessed. Evaluation of the mineral composition showed that the level of sodium, calcium, and potassium was high in both the processed and unprocessed sample (150–400 mg/100 g). However, the level of iron, copper, zinc, and magnesium was low in both processed and unprocessed samples (2–45 mg/100 g). The correlation analysis showed that tannins and oxalate affected the levels of ash and nitrogen-free extract of processed and unprocessed seeds. These results suggest that the consumption of S. stenocarpa will go a long way in reducing the level of malnutrition in northern Nigeria.